Bilinguismo e o Distúrbio Neurocognitivo causado pelo Alzheimer - Pains, Diana Elisandra Buscke (2023)
Bilingualism has been the subject of study in the context of cognitive neuroscience due to its potential impact on the prevention and mitigation of neurocognitive disorders, such as Alzheimer's. Bilingual individuals tend to develop the disease at a later age compared to monolingual individuals. Thus, from a bilingual perspective, this qualitative, literaturebased study investigated how bilingualism may delay the symptoms of Alzheimer's through studies involving both monolingual and bilingual patients. Researcher Ellen Bialystok, through her theories, argues that regular use of two languages stimulates the brain, advocating that bilingualism promotes a cognitive reserve that can postpone the onset of Alzheimer's symptoms. Furthermore, bilingualism appears to enhance brain plasticity and improve the ability to cope with cognitive decline. Although bilingualism is not a cure for Alzheimer's, it illustrates the complex interaction between language, the brain, and neurodegenerative diseases, providing valuable insights into prevention strategies.